Covalent Organic Framework Nanocarriers of Singlet Oxygen for Oxygen‐Independent Concurrent Photothermal/Photodynamic Therapy to Ablate Hypoxic Tumors. Issue 37 (15th August 2022) - Dutta, Debabrata; Wang, Jingbo; Li, Xiang; Zhou, Qinghao; Ge, Zhishen
Abstract: Photodynamic therapy (PDT) of cancers is seriously restricted by tumor hypoxia. In addition to the intrinsic hypoxic microenvironment, continuous photoirradiation further aggravates intratumoral hypoxia, thereby reducing the PDT effect significantly. Oxygen‐independent PDT is recognized as an efficient approach to overcome this issue. Herein, singlet oxygen ( 1 O2 )‐stored covalent organic framework (COF) nanoparticles loading the near‐infrared (NIR) dye cypate, which realize oxygen‐independent 1 O2 production for concurrent photothermal therapy (PTT) and PDT under NIR irradiation, are presented. The cypate‐loading COF nanoparticles are prepared by using the photosensitizers and 1 O2 ‐stored molecules via formation of Schiff base bonds, followed by coverage of poly(vinyl pyrrolidone). The COF nanoparticles significantly improve the photostability and photothermal conversion efficiency of cypate by protecting them from photodegradation under NIR irradiation. Upon 660 nm laser irradiation, 1 O2 is produced by the photosensitizer motifs and is successfully stored by the 1 O2 ‐stored moieties. After intravenous injection and tumor accumulation, the COF nanoparticles can generate heat quickly upon 808 nm irradiation which induces the efficient release of the stored 1 O2 to ablate tumors via O2 ‐independent concurrent PTT/PDT. Accordingly, the COF nanocarriers of 1 O2 provide a paradigm to develop O2 ‐independent concurrent PTT/PDT for precise cancer treatment upon NIR irradiation. Abstract : Cypate‐loaded covalent organic framework nanocarriers are constructed for storage and release of singlet oxygen ( 1 O2 ) in a controlled manner. The nanoparticles can produce and store 1 O2 upon exposure to 660 nm laser irradiation under normoxia, and release 1 O2 inside hypoxic tumors through the photothermal effect under 808 nm irradiation, which achieve oxygen‐independent concurrent photothermal and photodynamic therapy toward hypoxic tumors.